Sistem Informasi Administrasi Pembinaan K3 Menggunakan Metode SDLC Pada PT. Candi Talang Abadi - Adilah Qurroh A'yuniyah; Dede Sahrul Bahri (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Information system is a system that combines human activities and the use of technology to support management and operational activities. Where, there is a relationship created based on human interaction, data, information, technology, and algorithms. PT. Candi Talang Abadiis an Occupational Safety and Health Service Company (PJK3) in the field of K3 coaching and training. This company has many classes in the field of coaching and K3 training, with many coaching classes available making this company has a lot of administrative output data. This research uses Systems Development Life Cycle (SDLC) method. The source of data obtained by distributing questionnaires to employees. The result of this research is a web-based application system designed using PHP and HTML programming languages. The use of this application system is a solution to facilitate the process of inputting incoming and outgoing certificate data, making it easier to find data and reports produced more effectively.